2017
DOI: 10.3389/fcimb.2017.00415
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Signals of a Human Epithelial Colorectal Adenocarcinoma (Caco-2) Cell Line Facilitate the Penetration of Pseudomonas aeruginosa PAO1 Strain through the Mucin Layer

Abstract: Pseudomonas aeruginosa can penetrate the layer of mucus formed by host intestinal epithelial cells, often resulting in sepsis in immunocompromised patients. We have previously demonstrated that P. aeruginosa can penetrate the mucin layer by flagellar motility and the degradation of the mucin layer. However, it remains unclear how P. aeruginosa initially recognizes epithelial cells. Using the human epithelial colorectal adenocarcinoma (Caco-2) cell line, we investigated extracellular signaling that could facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…aeruginosa colonies in the bottom chamber exposed to sulfated vizantin (1 and 10 μM) as compared with untreated cells ( Fig 1A ; P > 0.05). As previously reported [ 8 , 22 ], deletion of the fliC gene significantly decreased the number of P . aeruginosa colonies in the bottom chamber ( Fig 1A ; P < 0.05).…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…aeruginosa colonies in the bottom chamber exposed to sulfated vizantin (1 and 10 μM) as compared with untreated cells ( Fig 1A ; P > 0.05). As previously reported [ 8 , 22 ], deletion of the fliC gene significantly decreased the number of P . aeruginosa colonies in the bottom chamber ( Fig 1A ; P < 0.05).…”
Section: Resultssupporting
confidence: 86%
“…We previously demonstrated that P . aeruginosa PAO1 penetrates the mucin layer by flagellar motility and a mucin degrading protease [ 8 , 22 ]. In the present study, sulfated vizantin (100 μM, 3 h incubation) did not significantly decrease bacterial protease activity ( Fig 2A ; P > 0.05), although protease inhibitors significantly decreased bacterial protease activity in P .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 122 A recent in vitro study, using the human colorectal adenocarcinoma cell line Caco-2, demonstrated that unidentified low molecular weight proteins present in the supernatant of Caco-2 cultures, also attracted P. aeruginosa in capillary chemotaxis assays and increased bacterial motility and mucin penetration (bovine submaxillary mucin). 123 Thus, there is growing evidence to suggest there is a link between production of chemoattractant molecules, motility of pathogens and their ability to colonise mucosal layers.…”
Section: Introductionmentioning
confidence: 99%